The environmental price of diagnostic scale-up—addressing a toxic trade-off we cannot afford - Odhiambo, Collins Otieno; Van Puije, Beatrice; Krisiunas, Edward; Mataka, Anafi (Frontiers in Lab on a Chip Technologies, 2025)
The scale up of diagnostic service in many Low-Income Countries (LIC) has greatly improved health outcomes of the populations being served by 21st century laboratory platforms like those seen in High Income Countries (HIC). A challenge because of this scale up is the contribution of increased volume of plastic and hazardous chemical waste that needs to be properly managed with limited options as compared to what is available in HIC. Guanidinium thiocyanate (GTC), as an example, a widely used component of extraction reagents used in Polymerase Chain Reaction (PCR) testing, when inappropriately disposed of can cause harm to animals and the environment because it contains a toxic cyanide compound. While environmental short term disposal methods exist that would improve the practices and offer alternative waste treatment options, challenges in availability of required infrastructure and sustainability remain, thereby limiting their impact. While testing generates revenue, waste associated with testing is a cost that is not adequately funded hence unsustainable in the current environment. The availability of alternative compounds that are less toxic yet can achieve the required actions may provide a lasting solution. Developing platforms geared towards microchemistry as well as the recyclability of the materials used for testing would steer waste/material management in a new direction. We call on diagnostic manufacturers to consider these options upstream of the product lifecycle in the long term that are in line with their internal corporate commitment to sustainability beyond the manufacturing process.